Development of Kita Kompeten Website as Information Media and Digital Workforce Training Registration - Fajar Akhmad Triyanto; Syalsabila Tia Monica (Applied Business and Administration Journal, 2026)
In the era of digital transformation, vocational training institutions need professional online communication media to expand access, increase information transparency, and strengthen organizational image. This research aims to design and develop the official website of Kita Kompeten as the main platform for delivering training information, participant registration, and strengthening public trust. The website is designed using WordPress CMS with a page structure including: homepage, login/register, class catalog, partners, and institution information page. Development was conducted using the Waterfall model approach which includes the following stages: needs analysis, design, implementation, testing, and maintenance. Visual data and feature documentation are shown as evidence of responsive and functional system implementation. The final results show that the website is able to fulfill the function as a digital information center, facilitate the registration process, display training catalogs, and strengthen institutional communication. This website is expected to be the initial model of digitalization of competency-based training institutions.